2015
DOI: 10.7314/apjcp.2015.16.6.2161
|View full text |Cite
|
Sign up to set email alerts
|

Sequence to Structure Approach of Estrogen Receptor Alpha and Ligand Interactions

Abstract: Estrogen receptors (ERs) are members of 7-transmembrane receptors such as steroid hormone receptor subfamily, G protein coupled receptor family, and nuclear hormone receptor superfamily. The amino acid sequences are different in types and depend on species (Kumar and Thompson, 1999;Kumar et al., 2011). There are two subtypes of estrogen receptor; ERα and ERβ (Kuiper et al., 1997;Barkhem et al., 1998). The genes encoding ERs located on different chromosomes, which are species specific. For example, ERα locates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…By contrast, the previous study using human ERα luciferase reporter gene assay revealed that none of these metabolites displayed estrogenic potency . This may be attribute to the difference between the rat and human ERα, despite the very similar sequence of these two receptor …”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…By contrast, the previous study using human ERα luciferase reporter gene assay revealed that none of these metabolites displayed estrogenic potency . This may be attribute to the difference between the rat and human ERα, despite the very similar sequence of these two receptor …”
Section: Discussionmentioning
confidence: 61%
“…26 This may be attribute to the difference between the rat and human ERα, despite the very similar sequence of these two receptor. 39 As for MR, the parent TDCIPP and TPHP inhibited MR signaling, and TCIPP has no interaction with MR. 21 The antagonistic potency of BDCIPP was roughly 21-fold higher than its parent chemical. Also, the BCIPP developed its antagonistic effect on MR at a low concentration (RIC 20 = 8.1 × 10 −7 M).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the high degree of sequence identity between the human and rodent ERα-LBD proteins, it has been tacitly assumed that the 3D structures and ligand-binding characteristics of these receptors are essentially identical across species [75, 76]. Indeed, in tests of estrogenic potential, a common scenario is to conduct ligand-binding assays using human receptors in vitro and to carry out in vivo assessments in rodents [7780].…”
Section: Discussionmentioning
confidence: 99%
“…We characterized, in some detail, the effects of two of these five drugs, hexestrol and clomifene, as, in addition to efficiently suppressing the growth defect of the msp1 P300S strain, they present less toxicity at high concentrations. Hexestrol has been used for years to treat estrogen deficiency and is one of the most potent known estrogens (Chamkasem and Toniti, 2015; Solmssen, 1945). Clomifene induces ovulation and has been used as such to treat various cases of female infertility (Kistner, 1965; Wilkes and Murdoch, 2012).…”
Section: Discussionmentioning
confidence: 99%